Review of the Civil Code and Compilation of Islamic Law on the Grant of All Property to Adopted Children - Muhammad Hafiz Umul Husni; Nur Iqbal Khambali; Yusrizal Amir Syah; Ade Jamarudin; Imam Sucipto (Zona Law And Public Administration Indonesia, 2023)
In Indonesia itself there is legal pluralism in the inheritance law section. Among them there is inheritance law based on Islamic inheritance law, inheritance law based on civil inheritance law. Grant or will is one way or effort in terms of transfer of property according to Islamic Law. A grant is a gift of property that occurs during the grantor's lifetime, while a will is a gift of property that occurs after the testator's death. Both of these instruments are encouraged in Islam, where if they are done correctly and in accordance with the requirements of the conditions then it can avoid disputes and struggles over property. The writing of this journal is carried out using normative juridical and empirical juridical methods where normative juridical is carried out by basing on applicable laws and regulations while empirical juridical is based on the implementation of laws and regulations that apply to society. The results of this study state that the relationship between grants and inheritance according to the Compilation of Islamic Law and the Civil Code is due to the transformation of Customary Law into Islamic Law (Article 211) of the Compilation of Islamic Law. A grant from a parent to his child can count as an inheritance. In the Civil Code, the relationship between grant and inheritance has existed since the creation of the Civil Code and the Compilation of Islamic Law itself. This is in the interest of all Indonesians